Venezuelan migration and the challenges of children's citizenship in Ibagué - GUTIERREZ, Juan Andrés; ARENAS, Andrea (Utopía y Praxis Latinoamericana, 2025)
This article aims to analyze the situation of children born to Venezuelan migrants in Ibagué, focusing on the challenges they face in accessing basic rights and how this affects their integration into Ibagué's society. Additionally, it explores the implications of these challenges for the reconfiguration of citizenship, offering reflections to better understand the social and political dynamics emerging in this context. The goal is to provide a critical perspective that contributes to the development of inclusive policies aimed at improving the quality of life for both migrants and the local population.